2015
DOI: 10.1016/j.ahj.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for risk stratification of patients with ST-elevation myocardial infarction treated with primary percutaneous coronary intervention: Insights from the Platelet Inhibition and Patient Outcomes trial

Abstract: Biomarker measurement on admission is feasible and provides incremental risk stratification in patients with STEMI treated with PPCI, with NT-proBNP and GDF-15 being most valuable due to the association with both CVD and spontaneous MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…GDF‐15 was measured with a precommercial assay (Roche Diagnostics) using a monoclonal mouse antibody for capture and a monoclonal mouse antibody fragment for detection in a sandwich assay format. The results of these analyses in relation to outcomes and effects of study treatment have previously been reported 8, 9, 10…”
Section: Methodsmentioning
confidence: 91%
See 4 more Smart Citations
“…GDF‐15 was measured with a precommercial assay (Roche Diagnostics) using a monoclonal mouse antibody for capture and a monoclonal mouse antibody fragment for detection in a sandwich assay format. The results of these analyses in relation to outcomes and effects of study treatment have previously been reported 8, 9, 10…”
Section: Methodsmentioning
confidence: 91%
“…Several biomarkers, on admission for ACS, provide clinically important information on risk for cardiovascular morbidity and mortality, including NT‐proBNP (myocardial dysfunction),9, 10 cardiac troponins (myocardial necrosis),29 and cystatin C (kidney function) 7, 11. Circulating osteoprotegerin has been reported to be associated with cardiovascular outcomes, including mortality, MI, and incident heart failure, in several ACS cohorts 16, 17, 18, 19.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations